The Threatful Self: Midbrain Functional Connectivity to Cortical Midline and Parietal Regions During Subliminal Trauma-Related Processing in PTSD. (September 2019) - Terpou, Braeden A.; Densmore, Maria; Théberge, Jean; Thome, Janine; Frewen, Paul; McKinnon, Margaret C.; Lanius, Ruth A.
Background: The innate alarm system consists of a subcortical network of interconnected midbrain, lower brainstem, and thalamic nuclei, which together mediate the detection of evolutionarily-relevant stimuli. The periaqueductal gray is a midbrain structure innervated by the innate alarm system that coordinates the expression of defensive states following threat detection. In participants with post-traumatic stress disorder, the periaqueductal gray displays overactivation during the subliminal presentation of trauma-related stimuli as well as altered resting-state functional connectivity. Aberrant functional connectivity is also reported in post-traumatic stress disorder for the default-mode network, a large-scale brain network recruited during self-referential processing and autobiographical memory. Here, research lacks investigation on the extent to which functional interactions are displayed between the midbrain and the large-scale cortical networks in post-traumatic stress disorder. Methods: Using a subliminal threat presentation paradigm, we investigated psycho-physiological interactions during functional neuroimaging in participants with post-traumatic stress disorder (n = 26) and healthy control subjects (n = 20). Functional connectivity of the periaqueductal gray was investigated across the whole-brain of each participant during subliminal exposure to trauma-related and neutral word stimuli. Results: As compared to controls during subliminal threat presentation, the post-traumatic stress disorder group showed significantly greater periaqueductal gray functional connectivity with regions of the default-mode network (i.e., angular gyrus, precuneus, superior frontal gyrus). Moreover, multiple regression analyses revealed that the functional connectivity between the periaqueductal gray and the regions of the default-mode network correlated positively to symptoms of avoidance and state dissociation in post-traumatic stress disorder. Conclusion: Given that the periaqueductal gray engages the expression of defensive states, stronger midbrain functional coupling with the default-mode network may have clinical implications to self-referential and trauma-related processing in participants with post-traumatic stress disorder.